Spray‐induced gene silencing targeting a glutathione S‐transferase gene improves resilience to drought in grapevine. (7th December 2021) - Nerva, Luca; Guaschino, Micol; Pagliarani, Chiara; De Rosso, Mirko; Lovisolo, Claudio; Chitarra, Walter
Abstract: Along with the ongoing climate change, drought events are predicted to become more severe. In this context, the spray‐induced gene silencing (SIGS) technique could represent a useful strategy to improve crop stress resilience. A previous study demonstrated that the Arabidopsis mutants for a glutathione S‐transferase ( GST ) gene had increased abscisic acid (ABA) levels and a more activated antioxidant system, both features that improved drought resilience. Here, we used SIGS to target a putative grape GST gene ( VvGST40 ). Then, ecophysiological, biochemical and molecular responses of 'Chardonnay' cuttings were analysed during a drought and recovery time‐course. Gas exchange, ABA and t ‐resveratrol concentration as well as expression of stress‐related genes were monitored in not treated controls, dsRNA‐ VvGST40 ‐ and dsRNA‐ GFP ‐ (negative control of the technique) treated plants, either submitted or not to drought. VvGST40 ‐treated plants revealed increased resilience to severe drought as attested by the ecophysiological data. Analysis of target metabolites and antioxidant‐ and ABA‐related transcripts confirmed that VvGST40 ‐treated plants were in a priming status compared with controls. SIGS targeting an endogenous gene was successfully applied in grapevine, confirming the ability of this technique to be exploited not only for plant protection issues but also for functional genomic studies. Summary Statement: Here, we used the innovative SIGS technique to functionally characterize a glutathione‐S‐transferase ( VvGST40 ) gene in grapevine which indeed showed an improved resilience when submitted to severe water stress treatment.